BENTUK PERGESERAN BAHASA JAWA MASYARAKAT SAMIN DALAM RANAH KELUARGA - Hari Mardikantoro (Faculty of Languages and Arts, Universitas Negeri Yogyakarta, 2012)
This study aims to describe the forms of the shift of Javanese in the Samin communityin the domestic domain. The data were collected from two locations where the Samincommunity lives, i.e. Tambak Hamlet, Sumber Village, Kradenan District and TanduranHamlet, Kemantren Village, Kedungtuban District. The data were ethnographicallyanalyzed. The findings show that there is a shift of Javanese in the Samin community from the ngoko Javanese to the krama Javanese. The ngoko language, which is the characteristic of Javanese in the Samin community, is used in a variety of domains. However, due to a variety of causes, the Samin community does not use the ngoko Javanese for all purposes. It is used only in the domestic domain and neighborhood involving the members of the Samin community only. In other domains such as social and educational domains, the ngoko Javanese is not used anymore and there is a shift to the krama Javanese.